2018
DOI: 10.1002/jrs.5422
|View full text |Cite
|
Sign up to set email alerts
|

Romantic restorations in the Alhambra monument: Spectroscopic characterization of decorative plasterwork in the Royal Baths of Comares

Abstract: The polychrome plasterwork decorations of the Room of the Beds in the Royal Bath of Comares of the Alhambra monumental ensemble have been studied using Raman microspectroscopy and complementary techniques. This area keeps the testimony of the controversial restorations carried out in the 19th century in an attempt to imitate the lost original appearance of the authentic Nasrid plasterwork. Raman spectroscopy and energy dispersive X-ray fluorescence have been employed to identify the pigments and extenders. Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The used pigments are natural malachite (K.10300) for probe 1 and cinnabar (K.42000) for probe 2 from Kremer Pigmente GmbH & Co.KG ® (Aichstetten, Germany) manufacturers. These pigments were selected taking into account the results from previous studies, as they are two of the most commonly found in work of this period [ 2 , 13 , 14 , 15 , 16 ]. Two binders were selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The used pigments are natural malachite (K.10300) for probe 1 and cinnabar (K.42000) for probe 2 from Kremer Pigmente GmbH & Co.KG ® (Aichstetten, Germany) manufacturers. These pigments were selected taking into account the results from previous studies, as they are two of the most commonly found in work of this period [ 2 , 13 , 14 , 15 , 16 ]. Two binders were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we added a layer of whitewash and selected various cleaning processes in order to test them. The base materials were selected taking into account previous work conducted by our team and other researchers in some of the most representative monuments of this period: Cuarto Real de Santo Domingo [ 13 ], the Madraza chapel [ 2 ], the plasterwork of the Alhambra [ 14 , 15 ], and the Real Alcazar of Sevilla [ 16 ]. Regarding the cleaning processes, we selected traditional methods, both physical (such as a scalpel) and chemical, and other techniques more recently used in restoration (polysaccharide-based gels, polyacrylic acids, or cellulose ethers).…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is now a well established analytical technique for the characterization of pigments and their substrates on frescoes, paintings, and on decorated artefacts comprising a range of materials, including wood, ceramics, and metals [27][28][29][30][31][32][33]. Even in complex mixtures the key spectral band signatures can be identified and correlated with the use of particular pigments either alone or in admixture [34,35] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…They found that using point‐by‐point Raman analysis with portable instruments showed agreement with the results obtained using the laboratory instruments. Arjonilla et al [ 128 ] considered Romantic restorations in the Alhambra monument and used spectroscopic characterization of decorative plasterwork in the Royal Baths of Comares. Klisinska‐Kopacz et al [ 129 ] found Raman spectroscopy to be a powerful technique for the identification of polymers used in cast sculptures from museum collections and found that portable Raman spectroscopy is a suitable technique for the identification plastics.…”
Section: Art and Archaeologymentioning
confidence: 99%